2019
DOI: 10.3390/pharmaceutics11040151
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of RGD–Cryptophycin Conjugates for Targeted Drug Delivery

Abstract: Cryptophycins are potent tubulin polymerization inhibitors with picomolar antiproliferative potency in vitro and activity against multidrug-resistant (MDR) cancer cells. Because of neurotoxic side effects and limited efficacy in vivo, cryptophycin-52 failed as a clinical candidate in cancer treatment. However, this class of compounds has emerged as attractive payloads for tumor-targeting applications. In this study, cryptophycin was conjugated to the cyclopeptide c(RGDfK), targeting integrin αvβ3, across the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 57 publications
0
34
0
Order By: Relevance
“…Cellular internalization was studied in vitro. M21 cells overexpress α v β 3 , whereas the variant M21L lacks α v and thus does not express α v integrins . As described previously, uptake of monomeric RGD peptides is fluid‐phase dependent, whereas for multimeric peptides internalization is clathrin‐dependent .…”
Section: Methodsmentioning
confidence: 70%
See 1 more Smart Citation
“…Cellular internalization was studied in vitro. M21 cells overexpress α v β 3 , whereas the variant M21L lacks α v and thus does not express α v integrins . As described previously, uptake of monomeric RGD peptides is fluid‐phase dependent, whereas for multimeric peptides internalization is clathrin‐dependent .…”
Section: Methodsmentioning
confidence: 70%
“…However, the pathway of uptake was only studied sparingly and reports are conflicting. For example, studies by us revealed colocalization of an RGD‐cryptophycin‐52 conjugate with lysosomes in WM‐115 cells (overexpressing α v β 3 ) and in contrast, an RGD‐cryptophycin‐55 conjugate was internalized both by M21 (overexpressing α v β 3 ) and M21L (α v knockout) cells . Likewise, cytotoxic RGD‐α‐amanitin conjugates did not provide specific uptake .…”
Section: Methodsmentioning
confidence: 94%
“…An alkyne‐functionalized PEG5‐linker was introduced to the N ‐terminus of the linker to allow the reaction with the azido‐functionalized monomeric ( 3 ) or tetrameric ( 4 ) integrin ligands (Scheme ). The conjugate 5 containing the monomer RGD ligand was synthesized as previously reported, whereas multimeric RGD compound 4 was achieved using a modular convergent strategy that involves the oxime ligation of aldehyde‐RGD and RAFT that displays 4 aminooxy groups (see the Supporting Information) …”
Section: Figurementioning
confidence: 99%
“…In recent years, considerable research efforts have been devoted to the development of SMDCs based on cryptophycins, afamily of microtubule targeting agents, that are characterized with outstanding potencya nd retained activity against multidrug-resistant (MDR) cancer cell lines. [24][25][26][27][28] Remarkably,t he synthetic cryptophycin-55 glycinate (1, Figure 1) displays adequate stability, exhibits cytotoxic activity in the subnanomolar range and showsh igh antitumor activity in vivo against MDR tumors. [26,29] We have previously reported that conjugates of monomeric c(RGDfK) ligandsa nd cryptophycin-55 glycinated isplayh igh potencya gainst the M21a nd M21-L human melanoma cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation